FITUR PAY LATER : KEBIASAAN BERHUTANG DAN KEIMPLUSIFAN BERBELANJA - Hidayati, Annisa; Carmenita, Carmenita; Puspitasari , Putri Mia (Jurnal Sosial-Politika, 2023)
The widespread use of E-Commerce in Indonesia, affects people's shopping habits. Companies E- Commerce also continue to innovate to retain their customers. Not only E-Commerce, ticket booking and accommodation places don't want to be left behind to follow this trend pay later. The Feature, pay later which was recently added to E-commerce and Ticketing services, is a shortcut for people who still want to shop and vacation even though they don't have money at that time. The implicitness of shopping and ordering using the pay later system without considering what will be the responsibility later, makes many people who are in debt in pay later. Many people still use pay later, even though they can't pay their bills every month. Users who cannot pay before the due date will be subject to a late penalty, this is also not able to deter debtors pay later. The desire to shop and fulfill desires is especially not caring if you have to go into debt first. The company's intelligence is to provide services that are profitable if they use the payment method pay later, for example free shipping services, so that sometimes it is used as an excuse for using pay later.